Glacial geomorphology of the northwest Laurentide Ice Sheet on the northern Interior Plains and western Canadian Shield, Canada ... - Dulfer, Helen E.; Stoker, Benjamin J.; Margold, Martin; Stokes, Chris R. (Taylor & Francis, 2023)
The majority of the Northwest Territories of mainland Canada was covered by the Laurentide Ice Sheet during the Last Glacial Maximum. The increasing coverage of high resolution remotely sensed data provides new opportunities to map the glacial geomorphology and study the glacial history of this remote location. Here we present a comprehensive map of glacial landforms within the northern Interior Plains and adjacent areas of the Canadian Shield, comprising around 6% of the Laurentide Ice Sheet bed. Twelve landform types were mapped from the high resolution ArcticDEM: ice flow parallel lineations, subglacial ribs, crevasse-squeeze ridges, major and minor moraine crests, hummocky terrain complexes and ridges, shear margin moraines, major, minor and lateral and submarginal meltwater channels, esker ridges and complexes, glaciofluvial complexes, perched deltas, raised shorelines and aeolian dunes. Together, these landforms provide a record of the highly dynamic behaviour of the northwest sector of the Laurentide ...